2008
DOI: 10.1590/s1516-35982008001300013
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte development in cattle: physiological and genetic aspects

Abstract: -Oocytes in cattle are formed during embryogenesis and develop within individual follicles in the cortex of the ovary. Dormant primordial follicles become active and undergo progressive development at regular intervals commencing during the late fetal stage and continuing throughout adulthood. Once activated, follicles and oocytes in a cohort either grow to maturation and ovulation or undergo atresia, ultimately depleting the ovaries of germ cells. It takes an estimated 100 days for a follicle and its oocyte t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…In the study by Moore et al (2005) (+++), the odds of PL during 35 to 41 d of gestation were 3.6 times higher in cows with DHIA test SCS >4.5 during the 30 d before AI compared with cows without mastitis (OR = 3.6; 95% CI = 1.0, 13.4). Although an explanation for this observed association was not reported in that study, we offer the following hypothetical explanation: subclinical mastitis can trigger a systemic inflammatory response that can affect follicular growth, oocyte quality, and embryo survival (Britt, 2008;Ribeiro et al, 2016). In Moore et al (2005) study, 381 pregnant cows were enrolled at the time of AI.…”
Section: Resultsmentioning
confidence: 89%
“…In the study by Moore et al (2005) (+++), the odds of PL during 35 to 41 d of gestation were 3.6 times higher in cows with DHIA test SCS >4.5 during the 30 d before AI compared with cows without mastitis (OR = 3.6; 95% CI = 1.0, 13.4). Although an explanation for this observed association was not reported in that study, we offer the following hypothetical explanation: subclinical mastitis can trigger a systemic inflammatory response that can affect follicular growth, oocyte quality, and embryo survival (Britt, 2008;Ribeiro et al, 2016). In Moore et al (2005) study, 381 pregnant cows were enrolled at the time of AI.…”
Section: Resultsmentioning
confidence: 89%
“…In ruminants, studies have confirmed that it takes months for a primordial follicle to reach the preovulatory stage (Britt 2008 ). It is known that oocytes from preantral follicles are growing and with an intense synthesis of RNA (Oktem and Urman 2010 ), which makes them sensitive to environmental changes.…”
Section: Discussionmentioning
confidence: 99%
“…The embryonic precursors of both the male and female gametes are the primordial germ cells (PGCs) -the undifferentiated cells that have the potential of developing into spermatozoa or oocytes (Edson et al, 2009). The fate of the germ cells is known during earliest stage of development stage, during cleavage or in the epiblast (Britt, 2008;Marlow, 2015;Downs, 2018). The germ cells then undergo two developmental stages.…”
Section: The Ovary and Folliculogenesismentioning
confidence: 99%